Green Supply Chain Management - Majeed, Mohammed, 1982-; Agarwal, Kirti; Tijani, Ahmed (Apple Academic Press, 2025)
Green supply chain management (GSCM) is the practice of integrating ecological sustainability processes that utilize the concept of the 4Rs (reduce, reuse, recycle, and reclaim) into the production, logistics, and end-of-life management of conventional supply networks. The book shows readers how to build a green supply chain by combining the efforts of operations management, purchasing, logistics, and marketing, and emphasizes looking outside the business to create long-term partnerships. The book covers key topics that include the benefits of GSCM and the factors and determinants of effective GSCM practices, along with discussions of green distribution, green procurement and purchasing, green logistics, green marketing, green warehousing, green transportation, and more. The authors present effective green supply chain management practices being used today and explore the role of industry 4.0 software tools in creating sustainable supply chain management in emerging markets.